HOX Gene Promoter Prediction and Inter-genomic Comparison: An Evo-Devo Study - Endriga, Maria A.; de la Paz, Victoria Karenina R.; Sazon, Jezreel Marie G.; Co, Elisa L.; Deocaris, Custer C. (Journal of Tropical Life Science, 2010)
Homeobox genes direct the anterior-posterior axis of the body plan in eukaryotic organisms. Promoter regions upstream of the Hox genes jumpstart the transcription process. CpG islands found within the promoter regions can cause silencing of these promoters. The locations of the promoter regions and the CpG islands of Homeo sapiens sapiens (human), Pan troglodytes (chimpanzee), Mus musculus (mouse), and Rattus norvegicus (brown rat) are compared and related to the possible influence on the specification of the mammalian body plan. The sequence of each gene in Hox clusters A-D of the mammals considered were retrieved from Ensembl and locations of promoter regions and CpG islands predicted using Exon Finder. The predicted promoter sequences were confirmed via BLAST and verified against the Eukaryotic Promoter Database. The significance of the locations was determined using the Kruskal-Wallis test. Among the four clusters, only promoter locations in cluster B showed significant difference. HOX B genes have been linked with the control of genes that direct the development of axial morphology, particularly of the vertebral column bones. The magnitude of variation among the body plans of closely-related species can thus be partially attributed to the promoter kind, location and number, and gene inactivation via CpG methylation.